Nursing Students' Satisfaction with and Experiences of Using Movies in Teaching Psychiatric Mental Health Nursing: A Mixed Methods Study. - Ahmed, Azza S. Z.; Dabou, Eman A. A. R.; El-Kader, Rabab G. Abd (Africa Journal of Nursing & Midwifery, 2022)
Movies have become a widely used educational tool in the medical and nursing fields. They have been understood to be facilitators of theoretical learning, cultural practices and awakening interests. Thus, it is necessary to understand students' experiences in using this advanced method. The present study aimed to assess nursing students' satisfaction with and experiences of using movies in teaching psychiatric mental health nursing. A cross-sectional mixed methods research design using a qualitative approach was used. A purposive sample was taken from 84 Year 1 Registered Nurse to Bachelor of Science in Nursing Bridge Programme students, recruited from a university in the United Arab Emirates during the 2018/2019 academic year. Two tools were used: (1) a self- administered sheet for participants' demographic data and satisfaction level; and (2) an interview schedule conducted as a focus group discussion according to the participants' preferences in order to assess their experiences. The questionnaire's content validity and the themes were revised by three PhD faculty who are specialists in the field of qualitative research and nursing education. The findings showed that most of the students were satisfied with using movies as a teaching strategy and the qualitative data fell into three themes and nine sub-themes. The students expressed that using movies allowed them to assess the environment where the patients lived and grew up. The study highlighted that nursing students found movies were an enjoyable educational method; helped them to understand psychiatric disorders; and improved their critical thinking skills. The study proved that using movies in teaching psychiatric mental health nursing is a promising strategy.